2018
DOI: 10.22159/ajpcr.2018.v11i1.19120
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Poorly Controlled Type 2 Diabetes Patients - Association of Patients’ Characteristics With Eq-5d Domains, Mean Eq-5d Scores, and Visaul Analog Scale Score

Abstract: Objective: High prevalence of diabetes mellitus in Malaysia demands the appropriate interventions to alleviate or postpone its burden on patients' health-related quality of life (HRQoL). The studies which provide useful knowledge about the components of such interventions are important. The aim of this study was to describe how demographic and clinical characteristics of diabetes patients influence their HRQoL using EQ-5D. Methods:This study used the baseline data of a randomized controlled study carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Of these, a total of 39 presented findings exclusively related to acute or long-term diabetes-related complications, 15 presented findings exclusively related to the influence of treatment-related attributes on QoL and 15 captured findings on both complications and treatment attributes. Therefore, a total of 30 articles presented utility/disutility values associated with treatment-related attributes or process characteristics ( Table 1 ) 7–36 These included a total of fifteen conducted in Europe, 9–11 , 13–15 , 19–21 , 24 , 25 , 29 , 31 , 33 , 34 eight conducted in Asia, 12 , 17 , 18 , 23 , 27 , 28 , 32 , 35 two in North America, 16 , 36 one in Latin America, 30 one in the Middle East, 8 one in Africa, 7 and two were multinational or the setting was not stated. 22 , 26 Most studies were conducted in people with T2D although three were conducted in general population samples 24 , 28 , 33 and one included both general population groups and groups with T2D.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, a total of 39 presented findings exclusively related to acute or long-term diabetes-related complications, 15 presented findings exclusively related to the influence of treatment-related attributes on QoL and 15 captured findings on both complications and treatment attributes. Therefore, a total of 30 articles presented utility/disutility values associated with treatment-related attributes or process characteristics ( Table 1 ) 7–36 These included a total of fifteen conducted in Europe, 9–11 , 13–15 , 19–21 , 24 , 25 , 29 , 31 , 33 , 34 eight conducted in Asia, 12 , 17 , 18 , 23 , 27 , 28 , 32 , 35 two in North America, 16 , 36 one in Latin America, 30 one in the Middle East, 8 one in Africa, 7 and two were multinational or the setting was not stated. 22 , 26 Most studies were conducted in people with T2D although three were conducted in general population samples 24 , 28 , 33 and one included both general population groups and groups with T2D.…”
Section: Resultsmentioning
confidence: 99%
“… 22 , 26 Most studies were conducted in people with T2D although three were conducted in general population samples 24 , 28 , 33 and one included both general population groups and groups with T2D. 29 The most frequently used elicitation method was the EQ-5D (3L or 5L), which was used in fourteen studies, 8 , 12–15 , 18 , 22 , 23 , 25 , 27 , 30 , 32 , 34 , 36 followed by TTO methodology used in ten studies, 10 , 11 , 16 , 19–21 , 24 , 26 , 29 , 33 then the Short Form 6 Dimensions questionnaire (SF-6D; three studies), 15 , 31 , 35 SG (three studies), 9 , 17 , 28 Health Utilities Index-2 (HUI-2; one study), 7 visual analog scale (one study), 17 Health Utilities Index-3 (HUI-3; one study) 7 and the 15D questionnaire (one study). 15 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies reported that patients who adhered to their treatment experienced an improvement in QoL and vice versa, as for a study conducted among epileptic patients [ 26 ], and another study among diabetic patients with type 2 diabetes [ 27 ]. This implies that good adherence to medications can provide good control of symptoms, resulting in an improved QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, a total of 39 presented findings exclusively related to acute or long-term diabetes-related complications, 15 presented findings exclusively related to the influence of treatment-related attributes on QoL, and 15 captured findings on both complications and treatment attributes. In total, 54 articles presented utility/disutility values for T2D-related complications (Table 1); these included a total of 18 studies conducted in Asia [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], 13 conducted in Europe [25][26][27][28][29][30][31][32][33][34][35][36][37], 13 in North America [38][39][40][41][42][43][44][45][46][47][48][49][50], 2 in Latin America [51,52], one in the Middle East …”
Section: Literature Searchesmentioning
confidence: 99%